Ekofeminisme Dalam Novel Tentang Kamu Karya Tere Liye - Fiter, Eru; Andriyani, Noni (J-LELC: Journal of Language Education, Linguistics, and Culture, 2021)
This research is motivated by several things, including the lack of studies on eco-feminism in novels in Indonesia, even in FKIP UIR there has been no research using the theory of eco-feminism. There are several ecofeminism studies that have been conducted before, but the data source used is by women, while ecofeminism research, which is the source of data, has never been done before. This study aims to describe, analyze, interpret, and conclude the eco-feminism in Tere Liye's novel About You, using Tong's eco-feminism study which includes several schools, namely (1) natural eco-feminism, (2) spiritualist eco-feminism, and (3) socialist eco-feminism. This research uses descriptive methods and content analysis techniques. The research data were obtained through a qualitative approach and using library research. The data in this research are in the form of words, phrases, clauses, sentences, and paragraphs that contain ecofeminism in them. The data source in this research is the novel About You by Tere Liye which was published in 2016 by the publishing agency Republika with a total of 524 pages and 33 chapters. The data collection technique in this research is the hermeneutic technique. The results showed that there was a flow of ecofeminism in Tere Liye's novel About You. The most dominant flow of eco-feminism is spiritualist ecofeminism because basically the lifestyle of caring women for nature often becomes a benchmark in everyday life to preserve the surrounding environment. Women and nature work together as partners in the process of sustaining life. On the other hand, the least flow is socialist ecofeminism because at this time the existence of socialist eco-feminism is very minimal acceptance among the community.